2011
DOI: 10.1007/s12199-011-0239-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate inhibits sphere formation of neuroblastoma BE(2)-C cells

Abstract: The present results suggest that EGCG may inhibit the development of TICs in BE(2)-C cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 28 publications
(33 reference statements)
3
23
0
Order By: Relevance
“…Our study showed that the expression levels of OCT4 strongly correlated with the stemness of NB I-type cells BE (2)-C. High expression of OCT4 increases grades and correlates with tumor progression and malignancy in glioma, a nervous system malignant tumor (8). With the overexpression of OCT4, BE (2)-C cells acquired increased proliferation rate and formed relatively more and larger sphere colonies on soft agar, indicating that OCT4 also played a role in increasing malignancy in BE (2)-C. This is consistent with a previous study that indicates BE (2)-C spheres grown in serum-free non-adherent culture show increased expression of OCT4 (16). In addition, we showed that with the downregulation of OCT4, BE (2)-C grew slowly compared with control, and was unable to form colonies on soft agar.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study showed that the expression levels of OCT4 strongly correlated with the stemness of NB I-type cells BE (2)-C. High expression of OCT4 increases grades and correlates with tumor progression and malignancy in glioma, a nervous system malignant tumor (8). With the overexpression of OCT4, BE (2)-C cells acquired increased proliferation rate and formed relatively more and larger sphere colonies on soft agar, indicating that OCT4 also played a role in increasing malignancy in BE (2)-C. This is consistent with a previous study that indicates BE (2)-C spheres grown in serum-free non-adherent culture show increased expression of OCT4 (16). In addition, we showed that with the downregulation of OCT4, BE (2)-C grew slowly compared with control, and was unable to form colonies on soft agar.…”
Section: Discussionsupporting
confidence: 90%
“…OCT4 has been used as a cell marker in NB to identify progenitor cells (12)(13)(14)(15)(16)(17). Our study showed that the expression levels of OCT4 strongly correlated with the stemness of NB I-type cells BE (2)-C. High expression of OCT4 increases grades and correlates with tumor progression and malignancy in glioma, a nervous system malignant tumor (8).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Green tea is a popular drink that is consumed by millions of people worldwide on a daily basis. In previous studies, EGCG demonstrated high cytotoxicity in cancer cells compared with normal cells and inhibited sphere formation by neuroblastoma cells . Takahashi A et al .…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma spheres were cultured as previously described (23). Briefly, neuroblastoma cells were cultured at 37˚C (5% CO 2 and 95% air) in sphere medium consisting of DMEM/Ham's F12 (3:1, Invitrogen), 100 units/ml penicillin/streptomycin (PC/SM; Invitrogen), 2% B27 supplement (Invitrogen), 40 ng/ml basic fibroblast growth factor (bFGF; R&D Systems, Minneapolis, MN), and 20 ng/ml epidermal growth factor (EGF; R&D Systems), subcultured by non-enzymatic cell dissociation solution (Sigma, St. Louis, MO), and maintained for >4 weeks in Ultra-low attachment culture dishes (CORNING, Corning, NY).…”
Section: Methodsmentioning
confidence: 99%